2017
DOI: 10.1111/cyt.12493
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing of BRAF, RAS and TERT on thyroid FNAs with indeterminate cytology improves diagnostic accuracy

Abstract: Mutation profiling can be successfully performed on thyroid LB-FNA without any dedicated sample in a pathology laboratory. It is an easy way to improve diagnostic accuracy of routine LB-FNA and may help to better select patients for surgery and to avoid unnecessary thyroidectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 34 publications
3
53
2
1
Order By: Relevance
“…Most publications included in our study accrued patients before the formal recognition of NIFTP, and these neoplasms would have been labeled follicular variant of PTCs and considered malignant. Of the publications in our analysis that reported NIFTP histology in their results (22,27,37,46,48,53,54,63,69), we considered them as ''malignant'' for statistical purposes, consistent with the current desire that they undergo surgical resection as opposed to in situ observation. Thus, PPVs in our study estimate the combined probably of cancer or NIFTP.…”
Section: Limitationsmentioning
confidence: 99%
“…Most publications included in our study accrued patients before the formal recognition of NIFTP, and these neoplasms would have been labeled follicular variant of PTCs and considered malignant. Of the publications in our analysis that reported NIFTP histology in their results (22,27,37,46,48,53,54,63,69), we considered them as ''malignant'' for statistical purposes, consistent with the current desire that they undergo surgical resection as opposed to in situ observation. Thus, PPVs in our study estimate the combined probably of cancer or NIFTP.…”
Section: Limitationsmentioning
confidence: 99%
“…Although >90% of thyroid nodules are non-neoplastic, 10 In this study, we reported the results of a prospective molecular analysis on 141 cytological samples of thyroid nodules with an indeterminate or frankly malignant cytological diagnosis to attempt a better management of the patients. Although this study concerns a small case series compared to more extensive studies, [28][29][30] possibility to perform molecular tests with an innovative, easy and low-cost method.…”
Section: Discussionmentioning
confidence: 99%
“…All of them were diagnosed with thyroid carcinoma, although it was not statistically significant due to the small sample size. Decaussin-Petrucci, et al 14) reported that neuroblastoma rat sarcoma (NRAS), harvey rat sarcoma (HRAS), and telomerase reverse transcriptase (TERT) gene mutations are strong predictors of malignancy regardless of the cytological classification according to the Bethesda system. According to the study in 61 AUS nodules, NRAS/HRAS mutations were significantly more frequent in malignant nodules and BRAF V600E mutation was not.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous reports suggested possible predictive factors, these studies enrolled very small patient numbers. 13,14) A large cohort study of AUS nodules followed by surgical pathologic confirmation providing statistically significant predictors for malignancy has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%